Uracil-DNA glycosylase of murine gammaherpesvirus 68 binds cognate viral replication factors independently of its catalytic residues - Kyle R. Smith; Somnath Paul; Qiwen Dong; Orchi Anannya; Darby G. Oldenburg; J. Craig Forrest; Kevin M. McBride; Laurie T. Krug (mSphere, 2023)
ABSTRACT Herpesviruses are large double-stranded DNA viruses that encode core replication proteins and accessory factors involved in nucleotide metabolism and DNA repair. Mammalian uracil-DNA glycosylases (UNG) excise deleterious uracil residues from their genomic DNA. Each herpesvirus UNG studied to date has demonstrated conservation of the enzymatic function to excise uracil residues from DNA. We previously reported that a murine gammaherpesvirus (MHV68) with a stop codon in ORF46 (ORF46.stop) that encodes for vUNG was defective in lytic replication and latency in vivo. However, a mutant virus that expressed a catalytically inactive vUNG (ORF46.CM) had no replication defect unless coupled with additional mutations in the catalytic motif of the viral dUTPase (ORF54.CM). The disparate phenotypes observed in the vUNG mutants led us to explore the non-enzymatic properties of vUNG. Immunoprecipitation of vUNG followed by mass spectrometry in MHV68-infected fibroblasts identified a complex comprising the cognate viral DNA polymerase, vPOL, encoded by ORF9, and the viral DNA polymerase processivity factor, vPPF, encoded by ORF59. MHV68 vUNG co-localized with vPOL and vPPF in subnuclear structures consistent with viral replication compartments. In reciprocal co-immunoprecipitations, the vUNG formed a complex with the vPOL and vPPF upon transfection with either factor alone or in combination. Lastly, we determined that key catalytic residues of vUNG are not required for interactions with vPOL and vPPF upon transfection or in the context of infection. We conclude that the vUNG of MHV68 associates with vPOL and vPPF independently of its catalytic activity. IMPORTANCE Gammaherpesviruses encode a uracil-DNA glycosylase (vUNG) that is presumed to excise uracil residues from viral genomes. We previously identified the vUNG enzymatic activity, but not the protein itself, as dispensable for gammaherpesvirus replication in vivo. In this study, we report a non-enzymatic role for the viral UNG of a murine gammaherpesvirus in forming a complex with two key components of the viral DNA replication machinery. Understanding the role of the vUNG in this viral DNA replication complex may inform the development of antiviral drugs that combat gammaherpesvirus-associated cancers.